Protective effect of date extract on rat nephrotoxicity induced by gentamicin, clinical, histological and antioxidant evidences - Celik, Ozgur Yasar; Irak, Kivanc (Cellular and Molecular Biology, 2018)
In this study, it was aimed to investigate the effect of the date extract (Phoenix dactylifera) on certain biochemical parameters and total antioxidant status (TAS), total oxidant status (TOS) and oxidative stress index in nephrotoxicity induced by gentamicin. The rats used in the study were randomly selected and divided into 4 groups, each consisting of 8 rats: control group, date extract (DE) group, gentamicin (GEN) group, gentamicin+date extract (GEN+DE) group. Blood samples and kidney tissues were taken 24 hours after eight days of trial. Urea, Creatinine, BUN, Na, Cl and K analyzes on the serum samples were carried out in auto analyzer. One of the kidney tissues was examined histopathologically. The supernatant, which was obtained by homogenizing the other kidney tissue was used in TAS and TOS analyzes. OSI was calculated using the formula. Urea, Creatinine, and BUN levels were higher in the GEN group, when compared to the other groups (p<0.001), while Na (p<0.05), Cl and K levels (p<0.001) were lower than those of the other groups. When the control group and the GEN group were compared, it was observed that the level of TAS decreased in the renal tissue and the level of TAS increased in the GEN+DE group. It was determined that TOS (p<0.01) and OSI (p<0.001) levels increased in the GEN group and renal TOS and OSI levels decreased in the GEN+DE group when compared to the GEN group. In conclusion, when the histopathological changes in kidney tissue with antioxidant and oxidant status in nephrotoxicity with gentamicin are examined, it can be said that date extract with gentamicin attenuates nephrotoxicity caused by gentamicin and date extract protects the kidney.